The raj and good governance: a story of acronyms - Bandyopadhyay, D. (2005)
The prime minister's speech at Oxford in July has sparked off a debate on the nature of "good governance" during the Raj. This article takes a tongue-in-cheek look at the special positions instituted by the Raj in the interests of good governance. It was in the 1930s and 1940s that the civil services created the "important" positions of LBAs, LBKs and the CCAs to ensure that concerns close to the heart of the then viceroy and the British prime minister received special attention. - Reproduced.
Keywords: Good governance; Public administration